The Impacts of Social Media on the Local Commercial Banks in Malaysia - Goi, Chai (ARRAY Development, 2014)
From a business and marketing perspective, the media landscape has dramatically changed with traditional media supplemented or replaced by social media (Yu et al, 2013). It has become an important method for banks to build relationships with their customers (Econsultancy, 2013). The main purpose of this paper is to review the impacts of social media on the banks, especially in terms of conversation, sharing, publishing and participation aspects. This paper also reviews the impacts of social media on the local commercial banks in Malaysia.